Palliative Care: Too Good to Be True? - Senderovich, Helen (Rambam Maimonides Med J, 2020)
INTRODUCTION: Many patients and their families are hesitant to consult a palliative care (PC) team. In 2014, approximately 6,000,000 people in the United States could benefit from PC, and this number is expected to increase over the next 25 years. OBJECTIVES: The purpose of this review is to shed light on the significance of PC and provide a holistic view outlining both the benefits and existing barriers. METHODS: A literature search was conducted using MEDLINE (PubMed), Cochrane Central Register of Controlled Trials, and Web of Science to identify articles published in journals from 1948 to 2019. A narrative approach was used to search the grey literature. DISCUSSION: Traditionally, the philosophy behind PC was based on alleviating suffering associated with terminal illnesses; PC was recommended only after other treatment options had been exhausted. However, the tenets of PC are applicable to anyone with a life-threatening illness as it is beneficial in conjunction with traditional treatments. It is now recognized that PC services are valuable when initiated alongside disease-modifying therapy early in the disease course. Studies have shown that PC decreased total symptom burden, reduced hospitalizations, and enabled patients to remain safely at home. CONCLUSION: As the population ages and chronic illnesses become more widespread, there continues to be a growing need for PC programs. The importance of PC should not be overlooked despite existing barriers such as the lack of professional training and the cost of implementation. Education and open discussion play essential roles in the successful early integration of PC.